Improving glycemic control: transitioning from dulaglutide to tirzepatide in patients with type 2 diabetes undergoing hemodialysis - Otsuka, Emiko; Kitamura, Mineaki; Funakoshi, Satoshi; Mukae, Hiroshi; Nishino, Tomoya (Frontiers in Pharmacology, 2024)
Background: Tirzepatide—a dual glucose-dependent insulinotropic peptide and glucagon-like peptide-1 receptor agonist—is used to treat type 2 diabetes. However, the efficacy and safety of tirzepatide in patients undergoing hemodialysis remain unclear. Methods: We conducted a single-center retrospective study of patients with type 2 diabetes undergoing hemodialysis who were transitioned from dulaglutide to tirzepatide. We continuously monitored glucose levels in patients undergoing hemodialysis before and after switching from dulaglutide to tirzepatide. Results: Fourteen patients (mean age: 61.9 ± 9.9 years, male: female = 11:3) were included in this study. After switching to tirzepatide, time in range increased to 50.8% from 42.7% (p = 0.02), time above range decreased to 37.8% from 48.4% (p = 0.02), and mean glucose levels decreased to 137.4 mg/dL from 156.6 mg/dL (p = 0.006). In contrast, there was no significant difference in time below range before and after tirzepatide administration (11.3% and 8.9%) (p = 0.75). Three patients experienced dyspepsia (21.4%), and one patient experienced nausea (7.1%); however, no critical adverse events were reported. Conclusion: Transitioning from dulaglutide to tirzepatide improved glycemic control without increasing hypoglycemia in patients undergoing hemodialysis for type 2 diabetes.